THE NEC2 RADIATION PATTERNS OF UNDER-SEGMENTED WIRE GRID MODELS OF A FIGHTER AIRCRAFT COMPARED TO MEASUREMENTS - Givati, 0. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
This paper presents results of a NEC2 method of moments evaluation of VHF/UHF antennas on a wire grid model of a fighter aircraft. The study shows that practically useful radiation patterns results can be obtained when the grid model is considerably under-segmented in aircraft regions which are electrically far removed from the antennas. Normal modelling guide-lines requires approximately 35000 segments for the fighter grid model at 400 MHz; judicious under-segmentation gave useful results using a model comprising 5000 segments. This reduction in segments reduced computer time by a factor of 343 and memory requirements is reduced by a factor of 18. NEC2 radiation patterns are compared to measurements on a l/lOth scale model which was performed in an anechoic chamber compact range. [Vol. 10, No. 1 (1995), pp 5-14]